Note—Optimal Portfolio Revision with Proportional Transaction Costs: Extension to Hara Utility Functions and Exogenous Deterministic Income - Constantinides, George M. (Management Science, 1976)
Kamin's theorem [Kamin, Jules H. 1975. Optimal portfolio revision with a proportional transaction cost. Management Sci. 21 (11, July).] on portfolio revision with proportional transaction costs is extended to allow for hyperbolic absolute risk averse investors and for the possibility of exogenous deterministic income, assuming that one of the two investment opportunities is riskless.